Peningkatan Hasil Belajar Pendidikan Pancasila Menggunakan Model Numbered Head Together di Kelas V SDN 03 Gunung Tuleh - Afwan, Zul; Masniladevi, Masniladevi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
The aim of carrying out this research is to develop student learning achievement in Pancasila education lessons using the Numbered Head Together (NHT) model in Class V SDN 03 Gunung Tuleh. The type of research that will be used is Action Research. The data collection techniques used to obtain valid data in classroom action research (PTK) are test and non-test techniques in the form of question sheets, teaching module assessment sheets, observation sheets, skills and attitude assessment rubrics. In the data analysis section, researchers used qualitative and quantitative data analysis techniques. This research uses a process which consists of designing, organizing, observing and contemplating. The subjects of this research were 15 fifth grade students, researchers as practitioners and class teachers as observers. The results of this research show that there has been an increase in aspects of planning, implementation and learning outcomes. Thus, the application of the NHT approach can improve student learning outcomes and is suitable for use in teaching Pancasila education for class V SDN 03 Gunung Tuleh.